Central European Functional Programming School 5th Summer School, CEFP 2013, Cluj-Napoca, Romania, July 8-20, 2013, Revised Selected Papers - Zsók, Viktória.; Zsók, Viktória.; Horváth, Zoltán.; Horváth, Zoltán.; Csató, Lehel.; Csató, Lehel. (Theoretical Computer Science and General Issues, 2015)
This volume presents the revised lecture notes of selected talks given at the Fifth Central European Functional Programming School, CEFP 2013, held in July 2013 in Cluj-Napoca, Romania. The 14 revised full papers presented were carefully reviewed and selected. The lectures cover a wide range of distributed and multicore functional programming subjects. The last 5 papers are selected papers of the PhD Workshop organized for the participants of the summer school.